Answer:
See Explanation
Step-by-step explanation:
![log(x + y) = log3 + \frac{1}{2} logx+ \frac{1}{2} logy \\ \\ log(x + y) = log3 + logx ^{\frac{1}{2}} + logy ^{\frac{1}{2}}\\ \\ log(x + y) = log3 + log(xy) ^{\frac{1}{2}} \\ \\ log(x + y) = log[3(xy) ^{\frac{1}{2}}] \\ \\ x + y = 3(xy) ^{\frac{1}{2}} \\ \\ squaring \: both \: sides \\ {(x + y)}^{2} = \bigg(3(xy) ^{\frac{1}{2}} \bigg)^{2} \\ \\ {x}^{2} + {y}^{2} + 2xy = 9xy \\ \\ {x}^{2} + {y}^{2} = 9xy - 2xy \\ \\ \purple{ \bold{{x}^{2} + {y}^{2} = 7xy}} \\ thus \: proved](https://tex.z-dn.net/?f=log%28x%20%2B%20y%29%20%3D%20log3%20%2B%20%20%5Cfrac%7B1%7D%7B2%7D%20logx%2B%20%20%5Cfrac%7B1%7D%7B2%7D%20logy%20%5C%5C%20%20%5C%5C%20log%28x%20%2B%20y%29%20%3D%20log3%20%2B%20%20%20%20logx%20%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%20%2B%20%20%20logy%20%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%5C%5C%20%20%5C%5C%20%20log%28x%20%2B%20y%29%20%3D%20log3%20%2B%20%20%20%20log%28xy%29%20%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%20%5C%5C%20%20%5C%5C%20log%28x%20%2B%20y%29%20%3D%20%20log%5B3%28xy%29%20%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%5D%20%5C%5C%20%20%5C%5C%20x%20%2B%20y%20%3D%203%28xy%29%20%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%20%5C%5C%20%20%5C%5C%20squaring%20%5C%3A%20both%20%5C%3A%20sides%20%5C%5C%20%20%7B%28x%20%2B%20y%29%7D%5E%7B2%7D%20%20%3D%20%20%5Cbigg%283%28xy%29%20%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%20%5Cbigg%29%5E%7B2%7D%20%20%5C%5C%20%20%5C%5C%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%20%20%7By%7D%5E%7B2%7D%20%20%2B%202xy%20%3D%209xy%20%5C%5C%20%20%5C%5C%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%20%20%7By%7D%5E%7B2%7D%20%20%3D%209xy%20-%202xy%20%5C%5C%20%20%5C%5C%20%20%20%5Cpurple%7B%20%5Cbold%7B%7Bx%7D%5E%7B2%7D%20%20%2B%20%20%7By%7D%5E%7B2%7D%20%20%3D%207xy%7D%7D%20%5C%5C%20thus%20%5C%3A%20proved)
Answer:
the graph is as illustrated above
The absolute value of x is shifting 3 units up
Answer:
5 cm
Step-by-step explanation:
Let's assume this is a number line were given.
Distance of S from 0 = 4 units
Distance of T from 0 = 9 units
Length of ST = the difference between T and S
ST = |9 - 4| = 5 units = 5 cm
This means S and T are 5 cm apart.
Answer:
y = x² + 3x - 40
Step-by-step explanation:
Given the zeros are x = - 8 and x = 5, then the factors are
(x + 8) and (x - 5) and
y = (x + 8)(x - 5) ← expand factors
y = x² - 5x + 8x - 40, hence
y = x² + 3x - 40 ← in standard form
Answer:
1. 81
2. 108 1/2
3. 189 1/2
Step-by-step explanation: